A multi-proxy detrital study from Permian-Triassic fluvial sequences of Victoria Land (Antarctica): Implications for the Gondwanan basin evolution - Zurli, Luca; Liberato, Giovanni Pio; Perotti, Matteo; Woo, Jusun; Jung Lee, Mi; Cornamusini, Gianluca (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)
One of the most complete Permian-Triassic fluvial sequences of the Beacon Supergroup, characterizing the infilling of the Transantarctic Basin, is recorded in the Allan Hills in Victoria Land (Antarctica). The multidisciplinary provenance approach carried out in this study includes UPb analysis on detrital zircons, chemistry ondetrital mineral phases (garnet and white mica), and sandstone petrography. These, coupled with the dataregarding the stratigraphic/sedimentological framework, provide a reconstruction of the geological history of thePermian-Triassic portion of the Beacon Supergroup, showing shifting clastic provenance from different sourcerocks. Results obtained from this integrated study support a source for the Permian Weller Coal Measures fromthe local basement, made up of very low- to high grade metamorphic rocks. A compositional shift is recordedwith the Lower Triassic Feather Conglomerate, mainly linked with changes in the fluvial style, likely associatedwith tectonic activity. The Middle to Upper Triassic Lashly Formation shows the main provenance change,supporting a distal source region: the fluvial system received a volcanoclastic input derived from the Permian-Triassic arc located to the east of the basin. The compositional and provenance variations, together with pale-ocurrent indicators, compared to the coeval units in the central Transantarctic Mountains, allow the recon-struction of the basin evolution and of the changing clastic drainage patterns. Data support the occurrence ofarticulated sub-basins where alluvial sedimentation settled, in which a morphological-structural divide wasrepresented by the Ross High, separating during the Permian up to the Early Triassic the Victoria Land sub-basinfrom the main Transantarctic Basin. According to the changed composition of the Lashly Formation sandstones, itappears that in the Middle/Late Triassic, the Ross High was not more a morphological barrier, and that theVictoria Land sub-basin was joined with the Transantarctic foreland Basin.